Analisis Masalah Kesehatan di Kota Bandar Lampung, Malaria Tetap Menjadi Masalah Utama - Nasyaroeka, Ayu Eka Buana Dewi; Sulistyawati, Sulistyawati; Kurniawan, Medi (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2024)
The Indonesian government wants to eradicate malaria in 2030. This suggests that throughout the previous three years, no native malaria cases had been discovered across the nation. It follows that every region needs to keep an eye on the malaria condition in its own territory. One of the areas with endemic malaria is Lampung Province. The purpose of this study is to analyze health issues and determine whether malaria is still a concern in Bandar Lampung City. USG was used to calculate the problem priority. Results, With an 80, malaria was found to be the main health problem. In conclusion, Bandar Lampung City's greatest challenge is still malaria. Keywords : Malaria Control, USG, Lampung, vector control, public health problem